Research and contemporary history taught in the Northern Patagonia - Funes, Graciela; Muñoz, María Esther (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article seeks to understand the potentialities of the teaching of contemporary history for the construction of multiple and democratic citizenries, which require an education for responsibility and participation driven by teachings with an ethical and political foundation. The research, which is of a qualitative nature, is carried out in public institutions of elementary and middle education in several cities of the provinces of Río Negro and Neuquén, and seeks to make a contribution to the knowledge about teacher training in history.   The teaching of contemporary history is highlycomplex, given that it is re-contextualized from multiple approaches. Thinking about the present historically implies an epistemological challenge and a reconsideration of the historiographical models. However, that does not mean a lack in the classrooms. Although being aware of the recent processes in teaching demands that teachers review and rethink things around these challenges, it would suppose that its importance is understood from the commitment to facilitate and favor the formation of active, critical and responsiblecitizens with present and future problems; issues approached in the framework of diverse and heterogeneous contexts.